2020
DOI: 10.1111/jgs.16882
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow in Patients with Severe Aortic Valve Stenosis Undergoing Transcatheter Aortic Valve Implantation

Abstract: BACKGROUND Transcatheter aortic valve implantation (TAVI) is a minimally invasive, life‐saving treatment for patients with severe aortic valve stenosis that improves quality of life. We examined cardiac output and cerebral blood flow in patients undergoing TAVI to test the hypothesis that improved cardiac output after TAVI is associated with an increase in cerebral blood flow. DESIGN Prospective cohort study. SETTING European high‐volume tertiary multidisciplinary cardiac care. PARTICIPANTS Thirty‐one patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“… 34 Recent studies show an immediate increase in cardiac output and cerebral blood flow following TAVR, suggesting a reserved or even decreased cerebral blood flow pre‐TAVR. 7 , 35 Our findings put forward the hypothesis that a chronic cerebral hypoperfusion pre‐TAVR may result into tolerance to an acute drop in IOH with a short duration during TAVR, a phenomenon called brain ischemic preconditioning. 36 , 37 , 38 Another factor that may explain our findings is the so‐called physiologic cerebral autoregulation, which alleviates a possible neurocognitive harmful effect of IOH.…”
Section: Discussionmentioning
confidence: 78%
“… 34 Recent studies show an immediate increase in cardiac output and cerebral blood flow following TAVR, suggesting a reserved or even decreased cerebral blood flow pre‐TAVR. 7 , 35 Our findings put forward the hypothesis that a chronic cerebral hypoperfusion pre‐TAVR may result into tolerance to an acute drop in IOH with a short duration during TAVR, a phenomenon called brain ischemic preconditioning. 36 , 37 , 38 Another factor that may explain our findings is the so‐called physiologic cerebral autoregulation, which alleviates a possible neurocognitive harmful effect of IOH.…”
Section: Discussionmentioning
confidence: 78%
“…Previous reports have shown improvement in neurocognitive functions following successful stenting in patient with carotid stenosis and abnormal cerebral perfusion, using the same battery of tests as the present study [ 31 33 ]. An association between increase in cardiac output and increase in cerebral blood flow in 31 patients following TAVR was found by Vlastra et al [ 5 ]. Schoenenberger et al reported cognitive improvement in patients with pre-TAVR aortic valve area less than 0.6 cm 2 [ 12 ].…”
Section: Discussionmentioning
confidence: 84%
“…Transcatheter aortic valve replacement (TAVR) has become an increasingly preferred alternative to surgical aortic valve replacement [ 1 , 2 ], and its indication is rapidly expanding to population with low-to-intermediate surgical risk [ 3 , 4 ]. Restoration of cardiac output after TAVR may lead to subsequent improvement in cerebral perfusion [ 5 ] and results in cognitive improvement. However, patients undergoing TAVR are at risk for early cerebrovascular events immediately after, or in the first few hours, following the procedure [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The association with valvular heart disease and delirium is novel and might be explained by older age, which predisposes a person to valve diseases. Moreover, we attribute this finding to reduced cerebral blood perfusion secondary to valve diseases ( 37 ), which is linked to delirium ( 38 ). Previous studies report a positive association of delirium with heart failure ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 98%